Survival characteristics and adjustment of MNE affiliates in the European integrated market - Antonios Georgopoulos; Felicitas Nowak-Lehmann D.; Vasilios Sogiakas (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2013)
This is one of the first studies which systematically investigate whether specific characteristics of foreign affiliates that reflect their MNE investment motivations prolong or undermine affiliate survivorship when the host country becomes member of a regional economic union. Using a unique database of 162 foreign affiliates established in the era of protectionism (1960-1980) in Greece, we explore the survival evolution of these affiliates within the European integration period (1981-2011). The study poses two research objectives: the exploration of the key characteristics per type of affiliate and the analysis of the impact of the specific characteristics on affiliate survival. We hypothesize and find that when the protected Greek economy enters the European market, closure risk is relatively high for those affiliates which exploit traditional location advantages such as tariffs and unskilled-labor cost, whereas it is relatively low for those units that adjust to the new institutional framework by investing in advertising and human capital intensity. The results have important implications for policy makers and managers.
Keywords: F15; F23; C25; 330; survival of MNE affiliates; protectionism; economic integration; Greece